Sustainable Innovations in Textile Chemical Processes (Textile Science and Clothing Technology,, 2018)
This book brings out the innovations in textile wet or chemical processing to alleviate the environmental impacts arising from this sector. The major challenge in the textiles and fashion sector is that it requires a massive sustainable innovation to mitigate the huge environmental impacts arising from chemical or wet processing. This book also discusses innovations in eco-friendly methods for textile wet processes and applications of enzymes in textiles.